Making Cross-Border Banking Work for Africa - Beck, Thorsten; Fuchs, Michael; Singer, Dorothe; Witte, Makaio (Eschborn, Germany: Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH, 2014)
Cross-border banking has been a critical part of Africa's financial history since colonial times. While the period after independence saw a wave of nationalization across the continent, with many of the colonial banks exiting, this trend was reversed in the 1980s with the arrival of financial liberalization. Failing state-owned and private banks were sold mostly to global investors or multinational banks. Increasing international and regional economic integration, including of financial services, and deregulation further increased the number of foreign banks and by the mid-2000s many African banking systems were yet again dominated by foreign banks. This introductory chapter documents trends in cross-border banking in Africa and the increasing shift in the composition of foreign banks in Africa. The next section provides a short overview of financial systems in Africa to set the stage. Section two characterizes the population of cross-border banks operating in Africa today, their expansion across the continent, and their importance in the host countries. Section three explores the reasons for the expansion of cross-border banking on the continent. Section four assesses the different business models banks use to expand across the continent as well as the characteristics of their group structures. Section five concludes.